2020
DOI: 10.1177/0003319720936925
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy and Vascular Complications in Diabetes Mellitus

Abstract: Vascular complications in patients with diabetes mellitus (DM) are common. Since impaired oxygen balance in plasma plays an important role in the pathogenesis of chronic DM-associated complications, the administration of hyperbaric oxygen therapy (HBOT) has been recommended to influence development of vascular complications. Hyperbaric oxygen therapy involves inhalation of 100% oxygen under elevated pressure from 1.6 to 2.8 absolute atmospheres in hyperbaric chambers. Hyperbaric oxygen therapy increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 140 publications
1
14
0
Order By: Relevance
“…It has been reported that the use of HBO in type 2 DM reduced hypoxia in tissues, reduced blood glucose, increased insulin secretion, increased target cell insulin sensitivity, and normalized an imbalance of the antioxidant system [15,16]. Until recently, there have been limited reports on the use of HBO in DR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the use of HBO in type 2 DM reduced hypoxia in tissues, reduced blood glucose, increased insulin secretion, increased target cell insulin sensitivity, and normalized an imbalance of the antioxidant system [15,16]. Until recently, there have been limited reports on the use of HBO in DR.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of oxidative processes causes the formation of a branched system protecting tissues from damage by aggressive oxygen radicals [superoxide anion radical (O2-), hydroxyl radical (HO-) and hydrogen peroxide Н2О2]. SOD family enzymes catalyze the dismutation of superoxide radicals into oxygen and hydrogen peroxide peroxide, and CAT catalyzes the conversion of hydrogen peroxide to water and molecular oxygen [11][12][13][14][15][16]. GSR provides restoration of the reduced form of glutathione [17], which significantly decreases the risk of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been already known that heterogeneity in microcirculatory blood perfusion and inadequate transport of oxygen to the microcirculation are closely related to the pathogenesis, and the development of diabetes and its complications 7 . However, the role of oxidative stress and hypoxia in T1DM is still a controversy, especially in the onset of T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…It has been already known that heterogeneity in microcirculatory blood perfusion and inadequate transport of oxygen to the microcirculation are closely related to the pathogenesis, and the development of diabetes and its complications. 7 However, the role of oxidative stress and hypoxia in T1DM is still a controversy, especially in the onset of T1DM. It is evident that hyperglycemia in T1DM individuals induces pathological alterations in endothelial cells, which may increase oxidative stress and contribute to endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%